Predykaty dyspozycyjne i definicje cząstkowe - Brykczyński, Piotr (Filozofia Nauki, 1997)
In the paper the methodological status of the partial definitions of dispositional predicates is considered. The problem of conservativeness, analyticity and of a pragmatic role of such definitions is analyzed.